2014
DOI: 10.1007/s11606-014-3136-y
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota’s Early Experience with Medical Home Implementation: Viewpoints from the Front Lines

Abstract: BACKGROUND:Evidence is evolving about the impact of patient-centered medical homes (PCMHs) on important outcomes in primary care. Minnesota has developed its own PCMH certification process, envisioned as an all-payer initiative with an emphasis on patientcenteredness, which may add unique experiences and outcomes to the national discussion. OBJECTIVE: We aimed to identify the facilitators and barriers encountered by nine diverse primary care practices selected from the first 80 to achieve PCMH certification in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…This is consistent with reports from other state-level programs where the use of control practices was used in various formats but not consistently across each domain. 21,22 Another limita- Continued tion is the limited observation period, from 2011 to 2013, which may include the period when practices were transforming to an NCQA-recognized PCMH and actual quality gains may be just starting to manifest. All NCQA-level achievement observations in the tables are from 2011/2012 in year 1, and ACG observations are also from 2011 data.…”
Section: Limitationsmentioning
confidence: 99%
“…This is consistent with reports from other state-level programs where the use of control practices was used in various formats but not consistently across each domain. 21,22 Another limita- Continued tion is the limited observation period, from 2011 to 2013, which may include the period when practices were transforming to an NCQA-recognized PCMH and actual quality gains may be just starting to manifest. All NCQA-level achievement observations in the tables are from 2011/2012 in year 1, and ACG observations are also from 2011 data.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the number of combined MD/MBA programs grew from six in 1993 to over 50 today, with over 500 graduates per year. 2 Nevertheless, the need remains great to prepare physicians to develop facility with speaking the language of health care finance, understanding health care policy and applying that knowledge and skill in the health care environment. A greater proficiency with the business side of health care will also help future physicians to responsibly address costs of care and at the same time innovate new policy approaches that optimize the wellbeing of patients and caregivers.…”
Section: Financesmentioning
confidence: 99%
“…2 These factors likely not only facilitate PCMH implementation, but also characterize knowledge and skills that physicians need to lead any meaningful systems change. How is medical education doing in addressing these domains of knowledge and skill?…”
mentioning
confidence: 99%
“…Early evidence suggests that practices that have involved patients in medical home transformation efforts view the engagement positively. 6,7 Attempts to engage patients in quality improvement efforts remain uncommon, however. A recent survey of 123 PCMHs found that fewer than one-third engaged patients in these efforts, although most of them reported soliciting patient input in other areas.…”
Section: Introductionmentioning
confidence: 99%